Implementasi Model Problem-Based Learning dengan Pendekatan Berdiferensiasi Berbasis Kemampuan Awal Siswa dan Teori Zone of Proximal Development (ZPD) untuk Meningkatkan Keaktifan Belajar di Kelas X TJKT SMK Negeri 1 Sukoharjo - Pawitra, Puruhita Mega; Budiyanto, Cucuk Wawan; Raharjo, Joko Slamet (Universitas Sebelas Maret, 2025)
This study aims to examine the effectiveness of implementing Problem-Based Learning (PBL) combined with differentiated instruction and the Zone of Proximal Development (ZPD) in enhancing student engagement in Grade 10 Technical Vocational High School students at SMK N 1 Sukoharjo. This quantitative research employed observation and questionnaire as research instruments. The results showed a significant increase in student engagement after the implementation of the learning model. The increase occurred in various aspects, such as active participation in discussions, independent task completion, and positive attitudes during the learning process. The combination of PBL, differentiated instruction, and ZPD proved effective in creating a more interactive and motivating learning environment for students. This study suggests the need for further research to expand the implementation of this learning model in various educational contexts.